Advokasi Nafkah Iddah bagi Perempuan Rentan: Peran LBH Perisai Keadilan Pemalang - Muchammad Danny Lutfi Maulana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The divorce rate, particularly divorce by talaq (religious divorce), in Pemalang Regency has increased year by year and reached 2,338 cases in 2022, raising questions about the fulfillment of post-divorce rights, particularly the provision of iddah (waiting period) for women divorced by their husbands. Fulfillment of these rights can be achieved through legal assistance, both at POSBAKUM (Public Legal Aid Institution) and legal aid institutions (LBH), which are mandated to provide free services. This study used a qualitative method with an empirical approach, where primary data was obtained through in-depth interviews with advocates at the Pemalang branch of LBH Perisai Sejati, and secondary data through books, journals, theses, and supporting documents. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results of the study indicate: first, LBH Perisai Sejati provides legal assistance in the form of assistance, defense, and representation of clients through litigation and non-litigation mechanisms. Second, this form of legal assistance complies with the provisions of Law No. 16 of 2011 concerning Legal Aid, specifically Articles 3, 4, 8, 12, and 18. Third, the services provided are considered effective based on Soerjono Soekanto's theory of Legal Effectiveness, because they are able to facilitate the fulfillment of iddah maintenance for women after divorce.